La esquina del futuro : escribir entre el barrio y la escuela - Dubin, Mariano (2015)
Distintos autores (Chartier, 1995, 1999; Chartier y Cavallo, 1998; Ginzburg, 2008; Sawaya, 2009) han señalado que las formas de leer corresponden a variaciones históricas y sociales. Considerando esta perspectiva, a partir de ciertos modos de la cultura barrial que se presentan en la escritura de alumnos en clases de lengua y literatura indagamos los marcos interpretativos de las lecturas de los jóvenes de la periferia urbana
Several authors (Chartier, 1995, 1999; Chartier y Cavallo, 1998; Ginzburg, 2008; Sawaya, 2009) have stated that the ways of reading are plural and diverse and, moreover, they are related to historical and social variations. Regarding this point of view, the current article analyses ways of working-class neighbourhood culture which appear in secondary school students' writing in the context of literature and language lessons and how it is useful for us as researchers to understand the teeneagers' reading interpretations
Keywords: Cultura popular; Cultura escolar; Escritura; Literatura; Barrios de la periferia; Popular culture; Scholar culture; Writing; Literature; Workingclass neighbourhoods